The Juridical Review of Oral Land Sale and Purchase Agreements in the Community According to Customary Law in Central Kalimantan - Amini, Cahaya Rusellia; Yestati , Ariani; Januardy, AIvans (Journal of Law, Politic and Humanities, 2025)
This research examines the juridical review of the practice of oral land sale and purchase agreements in indigenous communities in Central Kalimantan. Indigenous people still maintain oral-based sale and purchase mechanisms that are considered valid according to local customary law, as long as they are witnessed by traditional leaders and fulfill elements of trust and mutual agreement. Although recognized by custom, this kind of agreement has the potential to cause agrarian conflicts because it does not have sufficient evidentiary power before national law. This research uses a normative juridical approach, by reviewing legislation and interviews with indigenous community leaders. The results show that customary law and national law have common ground in the recognition of land rights, but there needs to be synchronization so that indigenous peoples do not lose their rights due to the lack of written evidence. This research emphasizes the importance of legal protection of local practices through formal recognition and recording mechanisms in accordance with local customary values